2023
DOI: 10.29303/jppipa.v9i1.1891
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study on The Scientific Literacy Skills of Prospective Biology Teachers

Abstract: Scientific literacy skills are very important skills in life, not only related to academic aspects, but also in real life. Therefore, science literacy skills become a goal in 21st century education. This study aims to investigate the level of scientific literacy skills of biology prospective teacher, and to find out whether there are significant differences in scientific literacy skills of biology prospective teacher based on semester. In this study, there were 69 prospective biology teachers as voluntary resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…When scientific literacy skills scores of the preservice science teachers were examined at the grade levels, it was understood that they had low proficiency in the first grade. The findings of other studies carried out with different study groups seemed to be consistent with this result and showed that individuals' scientific literacy skills are not proficient (for example, Adnan, Mulbar, Sugiarti & Bahri, 2021;Firdaus, Ibrohim, Lestari, Masiah, Primawati, & Hunaepi, 2023;Özdemir, 2010;Süren, 2008). In the evaluations made on the basis of all grades, it was observed that the average scores increased with the grade level, and there was a significant difference between 1 st and 3 rd , 4 th grades, and between 2 nd and 4 th grades.…”
Section: Discussionsupporting
confidence: 78%
“…When scientific literacy skills scores of the preservice science teachers were examined at the grade levels, it was understood that they had low proficiency in the first grade. The findings of other studies carried out with different study groups seemed to be consistent with this result and showed that individuals' scientific literacy skills are not proficient (for example, Adnan, Mulbar, Sugiarti & Bahri, 2021;Firdaus, Ibrohim, Lestari, Masiah, Primawati, & Hunaepi, 2023;Özdemir, 2010;Süren, 2008). In the evaluations made on the basis of all grades, it was observed that the average scores increased with the grade level, and there was a significant difference between 1 st and 3 rd , 4 th grades, and between 2 nd and 4 th grades.…”
Section: Discussionsupporting
confidence: 78%
“…Based on Table 3. 16, Scientific literacy test instruments have included indicators of scientific literacy, namely (1) evaluating the use of scientific information; (2) interpreting basic statistics; (3) graphical representation of the data; (4) solving problems using quantitative skills; (5) justifying the conclusions and predictions (Firdaus et al, 2023). The instrument is also adapted to the LO, namely finding the relationship between organ systems and their functions and abnormalities or disturbances that arise in the respiratory system of human organs so that it can be used in the Merdeka curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…(2) interpreting basic statistics; (3) graphical representation of the data; (4) solving problems using quantitative skills; (5) justifying the conclusions and predictions (Firdaus et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the importance of scientific literacy extends beyond academic contexts to everyday life, as well as globally (Holbrook & Rannikmae, 2009). As a result, scientific literacy research has gained popularity both globally and internationally (Firdaus et al, 2023).…”
Section: Introductionmentioning
confidence: 99%